An interleukin-6-induced acute-phase response does not confer protection against lipopolysaccharide lethality. - Bucklin, S E (1993)
Lipopolysaccharide (LPS), a component of gram-negative bacterial outer cell walls, can stimulate lymphoreticular cells to produce cytokines such as tumor necrosis factor alpha (TNF-alpha), interleukin-1 (IL-1), and IL-6. One of these proinflammatory cytokines, IL-6, induces hepatic synthesis of a class of proteins termed acute-phase proteins. D-Galactosamine inhibits acute-phase protein synthesis and concurrently sensitizes mice to a lethal dose of LPS approximately 10,000-fold. From these observations, we hypothesized that the acute-phase response may serve as a defense mechanism for protection of the host against the deleterious effects of LPS. To test this hypothesis, murine recombinant IL-6 (mrIL-6) was used to induce an acute-phase response prior to a lethal LPS challenge in both D-galactosamine-treated and normal mice. Induction of the acute-phase response by mrIL-6 was quantitated by measuring the concentrations of fibrinogen and complement component C3, two well-characterized acute-phase proteins, in the circulation. The effect of acute-phase and normal serum on TNF-alpha release by peritoneal macrophages stimulated with LPS in vitro was also examined. The results of these studies confirmed the induction of the acute-phase response by mrIL-6, as reflected in an approximate doubling in circulating levels of fibrinogen and C3. However, when either D-galactosamine-sensitized or normal mice were challenged with a lethal dose of LPS at various times after mrIL-6 administration, the acute-phase response induced by mrIL-6 did not alter either cumulative lethality or the kinetics of lethality. Additionally, compared with normal serum, acute-phase serum did not affect TNF-alpha release by peritoneal macrophages following LPS-mediated stimulation in vitro. Collectively, these studies would not support a dominant role for an IL-6-mediated acute-phase response as contributing to the resistance of normal mice compared with D-galactosamine-sensitized mice in LPS-induced lethal toxicity.